A descriptive cross-sectional study to assess prevalence of malnutrition in school children 6-14 years of age in rural and urban area of Bikaner, Rajasthan, India - Kumawat, Rakesh; Acharya, Rekha; Sharma, Gaurav; Sethia, Renu; Shekhawat, Kirti; Meena, Rattiram (International Journal Of Community Medicine And Public Health, 2017)
Background: Malnutrition affects the child’s physical and cognitive growth and increases the susceptibility to infections consecutively having an adverse impact on economic growth of the country indirectly therefore with 39% of the world’s malnourished living in India, we face a double jeopardy of malnutrition. The objective of this study was to determine the burden of malnutrition. Methods: A descriptive cross-sectional study was carried out among 720 school children in the age group 6 to 14 years from urban and rural areas in Bikaner district of Rajasthan from July 2014-December 2014 with the objective to assess prevalence and types of malnutrition. The sampling method used was stratified random sampling. The study tool used was a pre-tested questionnaire. Data analysis was performed with help of SPSS17.0. Results: The prevalence of underweight and overweight (based on weight for age) was found to be 19.72% and 0.70% respectively. 9.86% of the study population was found to be stunted. Thinness and obesity (based on BMI-for-age) was seen in 22.22% and 1.95% children. Hence overall prevalence of malnutrition was found to be 24.17%. Conclusion: Around one fourth of study population is affected from malnutrition which calls for urgent and prompt action in term of Primordial and Primary prevention.